2023
DOI: 10.3389/fnins.2023.1125208
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem volume changes in myalgic encephalomyelitis/chronic fatigue syndrome and long COVID patients

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and long COVID patients have overlapping neurological, autonomic, pain, and post-exertional symptoms. We compared volumes of brainstem regions for 10 ME/CFS (CCC or ICC criteria), 8 long COVID (WHO Delphi consensus), and 10 healthy control (HC) subjects on 3D, T1-weighted MRI images acquired using sub-millimeter isotropic resolution using an ultra-high field strength of 7 Tesla. Group comparisons with HC detected significantly larger volumes in ME/CFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 84 publications
3
4
0
Order By: Relevance
“…There was also an increase from the Mdul_L to a DM hub (DM.LP_R). The first result is consistent with a brainstem volume study ( Thapaliya et al, 2023 ) of the same subjects that reported larger volumes in LCov than HC. Both Mdul_L and CnF_R ROIs contain nuclei of the reticular activation system (RAS), an interconnected complex of small regulatory nuclei in the brainstem that influence cortical activity by both neurotransmitter release and oscillatory electrical stimulation.…”
Section: Discussionsupporting
confidence: 88%
“…There was also an increase from the Mdul_L to a DM hub (DM.LP_R). The first result is consistent with a brainstem volume study ( Thapaliya et al, 2023 ) of the same subjects that reported larger volumes in LCov than HC. Both Mdul_L and CnF_R ROIs contain nuclei of the reticular activation system (RAS), an interconnected complex of small regulatory nuclei in the brainstem that influence cortical activity by both neurotransmitter release and oscillatory electrical stimulation.…”
Section: Discussionsupporting
confidence: 88%
“…The aforementioned brainstem findings in long COVID-19 are consistent with its cognitive symptomology that largely revolves around fatigue and brain fog, reflecting prior reports of brainstem abnormalities in chronic fatigue syndrome (CFS) (Zhang et al, 2020a,b;Hugon et al, 2022;Thapaliya et al, 2023). Other neuroimaging findings are consistent with this clinical presentation as well, with diffusion weighted imaging (DWI) based microstructural changes reported in the thalamus -another region extensively implicated in CFS (Heine et al, 2023).…”
Section: Regarding Direct Sars-cov-2 Infiltration Of the Brainsupporting
confidence: 81%
“…Increased subcortical volumes in the context of chronic illness or pathology are suggested to be related to neurogenic inflammation or glial cell genesis, cell size increases, changes in cortical synaptic connectivity or changes in blood flow (Chen et al, 2019;Trachtenberg et al, 2002). In adults with ME/CFS, a recent study identified significantly larger volumes in the brainstem compared to healthy controls (Thapaliya et al, 2023) which, taken with our study, suggest increased volumes in autonomic regions may be implicated in ME/CFS pathophysiology. Another recent study also identified increased gray matter volumes in posterior cingulate cortex, precuneus and superior parietal lobule positively correlated with self-reported fatigue in adults recently discharged from hospital following infection with SARS-CoV-2, but were still experiencing symptoms of fatigue (Hafiz et al, 2022).…”
Section: Regional Hypothalamus Volumes and Fatigue Interactionssupporting
confidence: 80%